Shaping Policy: The Canadian Cancer Society and the Hormone Receptor Testing Inquiry - M. Mathews; J. Newbury; E. M. Housser (Current Oncology, 2011)
Background: In 2007, the Government of Newfoundland and Labrador established the Commission of Inquiry on Hormone Receptor Testing to examine problems with estrogen and progesterone hormone receptor tests conducted in the province between 1997 and 2005. Using the Inquiry as a case study, we examine the knowledge transfer activities used by the Canadian Cancer Society – Newfoundland and Labrador Division (CCS-NL) to shape policy and improve cancer control in the province. implementation: CCS-NL established a panel to advise its legal counsel and asked academic researchers to prepare papers to submit to the Commission. CCS-NL also interviewed patients to better inform its legal arguments, used its province-wide networks to raise awareness of the Inquiry, and provided a toll-free number that people could call. It also provided basic information, resources, and contact information for people who were affected by the flawed hormone receptor tests. The effectiveness of CCS-NL’s activities is reflected by the inclusion of its key messages in the Commission’s recommendations, and the investment in cancer care following the Inquiry. discussion: The success of the CCS-NL knowledge transfer efforts stemmed from its reputation as an advocate for cancer patients and its long-standing relationship with researchers, especially at the local level. The case illustrates real-world application of knowledge transfer practices in the development of public policy, and describes how community-based non-government organizations can identify and draw attention to important issues that otherwise might not have been addressed.